Relational Norms, Happiness and Customer Satisfaction in Micro Finance Institution’s (MFI’s): A Conceptual Framework - Rafiqul Islam, Shaikh; Perumal, Selvan; Hussin, Zolkafli (Journal of Advanced Research in Business and Management Studies, 2020)
The aim of this article is to discuss at conceptual level the relationships among the relational norms practices, happiness and customer satisfaction in Micro Finance Institution’s (MFI’s) of Bangladesh. Existing literature indicates that most of the studies on customer satisfaction in MFI in global as well as in Bangladesh context conducted on core dimensional (such as: product, interest rate, loan disbursement time, terms and condition etc.) issues where relational exchange context was ignored. The proposed conceptual framework which is drawn upon the existing literature has examined the effect of relational norm on both happiness and customer satisfaction. Moreover, happiness also has an influence on customer satisfaction. The marketing policy maker and other marketing consultants and practitioners certainly can improve the customer satisfaction by using this conceptual framework.